Effects of combined technology of micro-/nanobubble oxygenation irrigation and microbial agents on saline soil remediation and cotton yield - Bian, Qinyong; Yang, Yongxia; Ma, Liang; Ma, Yingjie; Wang, Zhiguo; Fu, Yanbo; Feng, Yaozu; Zhu, Jingquan; Wei, Yanhong; Lin, Ling (Frontiers in Plant Science, 2025)
Soil salinization severely limits Xinjiang cotton production sustainability, urgently requiring efficient, eco-friendly remediation. This study proposes a synergistic strategy of micro-nano bubble aeration + microbial agents (MA-MNBs) to improve saline-alkali soil via “physical aeration + biological regulation”. Field micro-plot experiments (completely randomized block, n=3) on Xinjiang saline-alkali cotton fields set 4 treatments: CK (conventional irrigation), MA (microbial agents), MNBs (micro-nano bubble irrigation), MA-MNBs (combination). Results showed: MA-MNBs significantly reduced soil salt by 26.08% vs CK (P<0.05); strongly activated soil enzyme activity (MA-MNBs > MA > MNBs); increased bacterial Chao1 index, enriched Proteobacteria/Actinobacteriota, and boosted Alternaria/Fusarium abundance; promoted cotton root growth, leaf area index, and dry matter accumulation (P<0.05); seed cotton yield reached 6278.65 kg·hm-² (44.53% higher than CK). Conclusion: MA-MNBs synergistically improves saline-alkali soil productivity by optimizing soil physicochemical and biological functions, providing an innovative solution for arid-region saline soil remediation and agricultural efficiency, as well as a theoretical basis for its mechanism and future application.